The Potential Therapeutic Effects of Platelet-Derived Biomaterials on Osteoporosis: A Comprehensive Review of Current Evidence - Mohammad Amin Amiri; Nima Farshidfar; Richard J. Miron; Arkadiusz Dziedzic; Shahram Hamedani; Sajad Daneshi; Lobat Tayebi (International Journal of Biomaterials)
Osteoporosis is a chronic multifactorial condition that affects the skeletal system, leading to the deterioration of bone microstructure and an increased risk of bone fracture. Platelet-derived biomaterials (PDBs), so-called platelet concentrates, such as platelet-rich plasma (PRP) and platelet-rich fibrin (PRF), have shown potential for improving bone healing by addressing microstructural impairment. While the administration of platelet concentrates has yielded positive results in bone regeneration, the optimal method for its administration in the clinical setting is still debatable. This comprehensive review aims to explore the systemic and local use of PRP/PRF for treating various bone defects and acute fractures in patients with osteoporosis. Furthermore, combining PRP/PRF with stem cells or osteoinductive and osteoconductive biomaterials has shown promise in restoring bone microstructural properties, treating bony defects, and improving implant osseointegration in osteoporotic animal models. Here, reviewing the results of in vitro and in vivo studies, this comprehensive evaluation provides a detailed mechanism for how platelet concentrates may support the healing process of osteoporotic bone fractures.